The irony of maqama "Summary nectar in describing of the fire" - العلي, منى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research aims to identify the phenomenon of paradox and its manifestations in the maqamat titled “Safou Al-Raheeq fi Description Al-Hariq” by its author, Ibn Al-Wardi. Irony allows the reader of prose text to enter his literary world and thus performs several functions. It is an effective threshold, and one of the keys to decoding the literary text. The research concluded that the paradox reflected the contrast between the state of Damascus before and after the fire, and this was represented by the contrast between the direct meaning of the spoken word and the indirect meaning. Ibn al-Wardi adopted the method of semantic accumulation of sub-contrasts within the maqamat to reach the pinnacle of paradox. As the writer deliberately and plans it through the contrast between the apparent and the hidden, it appears as a contradiction between what is said, what is written, and what is intended. In light the above, the research is divided into two parts; one is theoretical and aims to clarify the phenomenon of paradox in terms of language and terminology among Arabs and Westeres, with a quick overview of its most prominent types .The second is applied and studies the manifestations of paradox in one of Ibn al-Wardimaqama, represented by the paradox of title, the narrayors name,and the rhythm,inaddition to the paradox of pronunciation and meaning.